ASPEK RELIGIUS ISLAM DALAM NOVEL NAMAKU NAURA KARYA ALFINA DEWI - Marta, Ahmad; Nasution, Bakhtaruddin; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2014)
written in problems is this thesis is “Islamic religious aspects related to aqidah, Syariah and morals are reflected in the behavior of the characters in the novel My Name Naura Goddess Alfina work. Theory used in this study are as follows: (1) the nature of the literary wor, (2) novel, (3) a novel structure, (4) the scope of Islamic values. Research finding is as follows. (1) Islamic religious value in the novel My Name Naura on Aqeedah scope contained in Naura Goddess figures are: (a) God expects Rida, (b) believe that Allah is decisive and (c) belief God is giving instructions. Mohammed Fariz figures are in line with the Aqeedah is expecting the pleasure of Allah, believes God is decisive. The value contained in the aqidah side character named Nayla is learning Al - quran (2) In terms of Shari'ah contained on Naura Goddess figures are: (a) remembrance, (b) fasting (c) the prayer, and (d) istigfar. The value contained in the aqidah side character named Roby is prayer, went to the holy land. (3) The terms of the character contained in Naura Goddess figures are: (a) to say hello, (b) grateful, (c) beg forgiveness of Allah, (d) courtesy, (e) welcome the month of Ramadan, and (f) help. Mohammed Fariz figure that is in line with the character greetings, praying for others. Thes figures are in line with the morals Nayla is the character greetings, praying for others. The figures are in line with the morals Nayla is (a) never qive up, (b) play an accompaniment Rabbanablessings.